Evolution of Time Preference by Natural Selection - Rogers, Alan R. (American Economic Review, 1994)
This paper entertains the hypothesis that human time preferences are in evolutionary equilibrium (i.e. that no mutation changing time preferences could be favored by natural selection). This hypothesis implies that the marginal rate of substitution (MRS) holding Darwinian fitness constant must equal the MRS holding utility constant. Furthermore, in a market economy the latter must equal the MRS in exchange. Exploiting these principles, I find that the long-term real interest rate should equal ln(2) per generation (about 2 percent per year) and that young adults should discount the future more rapidly than their elders.